Curtain - Christie, Agatha, 1890-1976. (New York : Berkley Books, 2000)
Wheelchair-bound detective Hercule Poirot challenges his longtime friend Captain Arthur Hastings to find a killer at Styles Court, the site of their first case, before another victim falls.
Young Adult
Keywords: Poirot, Hercule (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Mystery fiction; Poirot, Hercule (Fictional character) -- Fiction; Private investigators -- Fiction; Mystery fiction